2022
DOI: 10.3390/cancers14246025
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA—A Novel Biomarker of Tumor Progression and Its Favorable Detection Techniques

Abstract: Cancer is the second leading cause of death in the world and seriously affects the quality of life of patients. The diagnostic techniques for tumors mainly include tumor biomarker detection, instrumental examination, and tissue biopsy. In recent years, liquid technology represented by circulating tumor DNA (ctDNA) has gradually replaced traditional technology with its advantages of being non-invasive and accurate, its high specificity, and its high sensitivity. ctDNA may carry throughout the circulatory system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 132 publications
(148 reference statements)
0
14
0
Order By: Relevance
“…Much of cancer research is centered on the analysis of nucleic acids [1]. DNA testing is considered to be the gold standard in cancer testing [2].…”
Section: Commentarymentioning
confidence: 99%
“…Much of cancer research is centered on the analysis of nucleic acids [1]. DNA testing is considered to be the gold standard in cancer testing [2].…”
Section: Commentarymentioning
confidence: 99%
“…Analysis of exosomes is benefit to the diagnose of tumor and prediction of the tumor prognosis (6). Previous study has shown that the exosomes secreted by tumors can enter into circulatory system and be detected in the blood (7). Separating the exosomes in the blood could realize the non-invasive way to identify the characteristics of tumors at an early stage and potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent CNAs in MYCN , 1q and 17p loci are considered good biomarkers for cancer monitoring through circulating tumor DNA (ctDNA) detection in liquid biopsy since they are reported in several pediatric malignancies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ] and can be identified using accessible methodologies, such as digital PCR (dPCR) and qPCR [ 25 ]. Although dPCR provides limited information regarding the profile of alterations, it has a low cost and high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…ctDNA levels are associated with the prognosis and may assist in the disease monitoring of patients diagnosed with a wide range of malignancies, e.g., prostate, breast, bladder and ovarian cancer [ 25 , 28 , 29 , 30 , 31 , 32 , 33 ]. In patients diagnosed with osteosarcoma, higher ctDNA levels were associated with a worse prognosis [ 34 ].…”
Section: Introductionmentioning
confidence: 99%